A major practicum report for Far East Seafood, Inc. Davao Fish Port Complex, Lizada, Toril, Davao City John Quindoy Miro. - Miro, John Quindoy (2008)
This manuscript seeks to present and document the student?s experiences, the information he obtained, and the lessons he learned during his 288-hour tenure at the Far East Seafood Inc., Davao Fish Port Complex, Lizada Toril, Davao City, from April to May 2008. In this practicum, the student was given the opportunity to see the practical application of the principles and concepts in books that he learned from the academe and see how they were treated in the tuna company?s daily operations. He was able to observe the duties and tasks that the Quality Control staff of the company performed and was also given the opportunity to carry out such tasks himself. These tasks included activities in the production area section namely; receiving, initial cutting, final cutting, packing and laboratory sections. The intern was also assigned in the warehouse and sales and marketing department of the company to make him familiar with the activities of the entire company in general. Moreover, he was able to gather relevant information not only about the activities in the activities in the production area but the entire company in general. Among such information are company?s historical background, organizational structure, mission and vision, tuna process flow, product analysis and waste management operations of the company. Lastly, the student was able to make recommendations on the activities in the production area particularly in terms of the company?s Quality Control